Clinical-pathological Study of Rosacea in a Small Cohort of Saudi Arabia - Amal O. Al-Balbeesi,; Maha M. Arafah,; Shaesta N. Zaidi, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Although rosacea is a common disease, it is rarely biopsied. There are few reports on the histopathological changes in rosacea in literature, but no attempt has been made in Saudi Arabia, to correlate such changes with clinical findings. In the present study, our aim was to analyze the clinical diversity and histological alteration of rosacea in a small cohort. The study included eight patients with a diagnosis of rosacea. A skin biopsy with 4 mm punch was performed in each case from the clinically involved area. The patients had broad clinical spectrum of lesions ranging from erythematous telangiectatic plaque to rhinophyma. No histological pattern was found to be unique for rosacea. Demodex mite infestation, which is considered to be significant in literature, was found not to be a contributing factor. Rosacea demonstrates a wide range of clinical presentation. Elastoid degeneration was an outstanding feature due to the ultraviolet sensitivity of the disease and the fact that our sunrays are potentially damaging all year round.